2018
DOI: 10.1097/ta.0000000000001983
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle crash fatalaties and undercompensated care associated with legalization of marijuana

Abstract: Prognostic, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
0
31
0
3
Order By: Relevance
“…59 73-77 However, studies assessing the impacts of cannabis regulation on overdose or poisoning by drugs other than cannabis concluded that the effects were either beneficial (four outcome measures 64 76 78 79 ) or mixed/null (three outcome measures [80][81][82] ). Driving with detectable concentrations of THC was most often found to increase following decriminalisation or legal regulation (five of eight outcome measures; [83][84][85][86][87] ), but these studies were of lower average quality (X=12.0).…”
Section: Impacts Of Decriminalisation and Legal Regulationmentioning
confidence: 99%
“…59 73-77 However, studies assessing the impacts of cannabis regulation on overdose or poisoning by drugs other than cannabis concluded that the effects were either beneficial (four outcome measures 64 76 78 79 ) or mixed/null (three outcome measures [80][81][82] ). Driving with detectable concentrations of THC was most often found to increase following decriminalisation or legal regulation (five of eight outcome measures; [83][84][85][86][87] ), but these studies were of lower average quality (X=12.0).…”
Section: Impacts Of Decriminalisation and Legal Regulationmentioning
confidence: 99%
“…Fluid and electrolyte disorders may be due to the higher prevalence of hyponatremia and hypokalemia, and dehydration due to intractable hyperemesis in patients with excessive cannabis use . Cannabis impairs coordination and concentration and reduces reaction time that causes driving problems and motor vehicle accidents . The Cambridge Study of Delinquent Development found that cannabis use increases the risk of convictions and violence behavior (OR, 7.1) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, users of marijuana, in particular heavy users, are more likely to have problems with use of alcohol and other drugs [53]. It has been demonstrated that acute marijuana smoking impairs driving performance [54], with an increase in motor vehicle fatalities linked to marijuana legalization [55]. Both short-term [56] and long-term [57] use can lead to cognitive performance decline.…”
Section: Discussionmentioning
confidence: 99%